Pengaruh Beban Kerja dan Work Life Balance terhadap Turnover intention yang di Mediasi Kepuasan Kerja - Muhammad Gendy Trialdy Kurniawan (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
The purpose of this study is to examine and determine: (1) the effect of workload on job satisfaction; (2) the effect of work–life balance on job satisfaction; (3) the effect of workload on turnover intention; (4) the effect of work–life balance on turnover intention; (5) the effect of job satisfaction on turnover intention; (6) the effect of workload on turnover intention through job satisfaction as a mediating variable; and (7) the effect of work–life balance on turnover intention through job satisfaction as a mediating variable. The population of this study consisted of all permanent employees of Bank Rakyat Indonesia (BRI) Kendari ByPass Branch, totaling 45 employees, all of whom were included as respondents. The data analysis technique used was path analysis, with the calculation process assisted by the SmartPLS program.The results indicate that: (1) workload has a negative and significant effect on job satisfaction; (2) work–life balance has a positive and significant effect on job satisfaction; (3) workload has a positive and significant effect on turnover intention; (4) work–life balance has a negative and significant effect on turnover intention; (5) job satisfaction has a negative and significant effect on turnover intention; (6) workload affects turnover intention through job satisfaction as a mediating variable; and (7) work–life balance has an indirect effect on turnover intention through job satisfaction.